The Impact Distribution of Zakat in Alleviating Poverty During COVID-19 Pandemic: Evidence From Indonesia - Dion Saputra Arbi; Jonathan Farez Satyadharma; Ihsan Hidayat (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2024)
Zakat is one of the Islamic socio-economic instruments to improve the welfare of Muslim communities by reducing poverty levels. Between 2020-2022, when the COVID-19 pandemic hit Indonesia, zakat management institutions succeeded in getting 1,145,636 people out of poverty, thereby increasing the achievements of mustahik to muzakki by augmenting individual and household sources of income from zakat recipients. This study uses the CIBEST analysis tool and the BAZNAS Welfare Index (IKB) to measure the impact of zakat distribution by BAZNAS on poverty alleviation during the COVID-19 pandemic in Indonesia. The results of this study indicate that zakat distribution can alleviate the poverty of the Indonesian population by 4.14 percent during the COVID-19 pandemic. Thus, the distribution of zakat funds during the pandemic era significantly reduced Indonesia’s poverty.